2021
DOI: 10.32674/jis.v11i2.1726
|View full text |Cite
|
Sign up to set email alerts
|

The First Year Acculturation: A Longitudinal Study on Acculturative Stress and Adjustment among the First Year International College Students

Abstract: We analyzed 192 first year international college students in Mid-Atlantic region to examine change of international students’ acculturative stress, adjustment, and collegiate experiences during their first year in the U.S. higher education. We found that male students, students from low socio-economic status, and students majored in humanity showed higher rate of acculturative stress and lower rate of satisfaction with college experiences compared to their counterparts. International students reported decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 66 publications
2
36
1
Order By: Relevance
“…At the same time, about 12% of our sample reported facing intercultural difficulties, but not necessarily internalizing symptoms. In combination with the maladjusted group, the percentage of individuals facing intercultural difficulties is largely consistent with research prior to the pandemic, which found that over half of international students experienced at least mild level of intercultural difficulties (e.g., Koo et al, 2021 ; Poyrazli & Lopez, 2007 ). It highlights the need for customized support among young adults, especially of those who were marginalized and vulnerable.…”
Section: International Students’ Psychosocial Well-being Profilessupporting
confidence: 83%
“…At the same time, about 12% of our sample reported facing intercultural difficulties, but not necessarily internalizing symptoms. In combination with the maladjusted group, the percentage of individuals facing intercultural difficulties is largely consistent with research prior to the pandemic, which found that over half of international students experienced at least mild level of intercultural difficulties (e.g., Koo et al, 2021 ; Poyrazli & Lopez, 2007 ). It highlights the need for customized support among young adults, especially of those who were marginalized and vulnerable.…”
Section: International Students’ Psychosocial Well-being Profilessupporting
confidence: 83%
“…In line with previous research ( Smith and Khawaja, 2011 ; Lopez and Bui, 2014 ), self-rated English proficiency was a significant predictor of international students’ acculturation experience. Different from some studies, which suggest that length of stay in the United States significantly shape international students’ acculturative stress levels ( Koo et al, 2021 ), the current findings indicate that the relationship was insignificant. One way to shed light on this finding is via gaining a deeper understanding of the scales studied.…”
Section: Discussioncontrasting
confidence: 99%
“…Gebregergis, Huang and Hong [2] reported that 506 international university students from seven Chinese universities experienced a higher level of acculturative stress with more significant depressive symptoms. Similarly, and Koo, et al [41] reported a higher level of acculturative stress among first-year international students enrolling in U.S. higher education. Likewise, and Musheer, Juni, Shahar and Ismail [17] reported that 78.5% out of 522 new postgraduate international students joining Malaysian Public Universities experienced a moderate level of acculturative stress, and 12.1% experienced a high level of acculturative stress, while 4.9% of them experienced a low level of acculturative stress.…”
Section: Introductionmentioning
confidence: 87%